An adapted thermal-gradient block for the germination of photoblastic seeds - Cardoso, Victor José Mendes [UNESP] (Brazilian Archives of Biology and Technology, 2010)
Este trabalho descreve um bloco termo-gradiente com iluminação interna, adaptado para estudos com sementes que requerem luz para germinar. Para se aferir o desempenho do equipamento, este foi usado num experimento sobre o efeito da temperatura na germinação de sementes fotoblásticas de Plantago tomentosa. Com o protótipo aqui descrito, alguns parâmetros da resposta dessa semente à temperatura puderam ser estimados, mostrando que o equipamento pode ser usado em estudos sobre a dependência térmica da germinação de sementes fotoblásticas.

This work describes an adapted thermal-gradient block with internal illumination, allowing experiments with light-requiring seeds. The temperature dependence study on the germination of the photoblastic Plantago tomentosa seeds was carried out in order to test the performance of the apparatus. With the aid of the model described here, some parameters related to the response of the seeds to temperature could be estimated, showing that the apparatus was suitable for the studies on the temperature dependence of photoblastic seeds.
Keywords: Temperature devices; thermal-biology; Plantago tomentosa